Light-emitting element and display device
By using nanoparticles with metal oxides in the light emitting element and forming an inorganic second material with low electron transport capability on their surfaces, the problems of excessive electrons and poor carrier balance are solved, the driving voltage is reduced and the process is improved Patience and reliability.
Patent Information
- Application Number
- CN202280096624.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing light emitting elements, the layer composed of inorganic materials has excessive electrons and poor carrier balance between the cathode and the light emitting layer, and metal ions or hydroxides may cause carrier deactivation and oxidation of the luminescent material, increasing Drive voltage and thickness.
Using nanoparticles with metal oxides as interposers, the inorganic second material with low electron transport capability is formed on the surface of the nanoparticles, the electron injection barrier is reduced and the carrier balance is improved, and the damage and driving voltage in the manufacturing process are reduced.
Reducing the driving voltage and improving carrier balance of the light emitting layer is achieved, reducing excessive electrons and the thickness of the light emitting element, while improving process resistance and reliability.
Smart Images

Figure CN119318233A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a light emitting element and a display device including the light emitting element. Background Art
[0002] Patent Document 1 discloses that a ZnO nanoparticle alloyed with Mg is used in an electron transport layer. 1-x Mg x O (0≤x≤0.5) and other Zn-containing metal oxide nanoparticles increase the band gap of ZnO nanoparticles and promote electron injection. In addition, Patent Document 1 discloses that the above structure can obtain a light-emitting element with higher luminous efficiency than using ZnO nanoparticles in the electron transport layer. Prior art literature Patent Literature
[0003] Patent Document 1: Korean Patent Application Publication No. 1020160033520 Summary of the invention Technical problems to be solved by the present disclosure
[0004] However, a light-emitting element having a layer made of an inorganic material between a cathode and a light-emitting layer generally has an excess of electrons and a poor carrier balance.
[0005] Furthermore, when the charge transport layer contains metal ions or hydroxides, carriers injected into the charge transport layer may be deactivated. Furthermore, the metal ions or hydroxides may oxidize the light-emitting material in the light-emitting layer and deactivate it.
[0006] For example, it is also possible to form a transport layer in which two materials having different carrier mobilities are mixed, or two transport layers containing the two materials are formed. In this case, there is a problem of damage to other layers in the process of forming a transport layer mixed with two materials, or an increase in driving voltage due to an increase in the thickness of the light-emitting element caused by forming two transport layers. Technical solutions for solving technical problems
[0007] A light-emitting element of one embodiment of the present invention includes: an anode; a cathode; a light-emitting layer located between the anode and the cathode; and an intermediate layer located between the light-emitting layer and the cathode, the intermediate layer having: at least one nanoparticle composed of a first material containing a metal oxide; and a second material portion formed on at least a portion of the surface of the nanoparticle and composed of an inorganic second material, the second material having a lower electron transport ability than the first material.
[0008] A light-emitting element of one embodiment of the present invention includes: an anode; a cathode; a light-emitting layer located between the anode and the cathode; and an intermediate layer located between the light-emitting layer and the cathode, the intermediate layer having: at least one nanoparticle composed of a first material, the first material including at least one of the group consisting of zinc oxide, magnesium zinc oxide, lithium zinc oxide, titanium oxide and strontium titanium oxide; and a second material portion formed on at least a portion of the surface of the nanoparticle and composed of a second material, the second material including at least one of the group consisting of magnesium oxide, zirconium oxide, aluminum oxide, yttrium oxide, silicon oxide, zinc sulfide, magnesium zinc sulfide and strontium sulfide.
[0009] A light-emitting element of one embodiment of the present invention includes: an anode; a cathode; a light-emitting layer located between the anode and the cathode; and an intermediate layer located between the light-emitting layer and the cathode, wherein the intermediate layer is formed by the following method, the method including: synthesis of a first solution, wherein the first solution contains at least one nanoparticle, and the at least one nanoparticle is composed of a first material; synthesis of a second solution, wherein a second material different from the first material is added to the first solution; formation of a second material portion, wherein the second material portion is formed on at least a portion of the surface of the nanoparticle by ultrasonic treatment of the second solution, and the second material portion is composed of the second material; and coating of the second solution, wherein the nanoparticle has at least one nanoparticle formed with the second material portion.
[0010] A display device according to one embodiment of the present disclosure comprises: a substrate; and a red light-emitting element, a green light-emitting element, and a blue light-emitting element on the substrate, wherein at least one of the red light-emitting element, the green light-emitting element, and the blue light-emitting element is any one of the above-mentioned light-emitting elements. Beneficial Effects
[0011] To achieve a light-emitting element and a light-emitting device capable of reducing damage to each layer during a manufacturing process and achieving both a reduction in driving voltage and an improvement in carrier balance in a light-emitting layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic cross-sectional view showing the light-emitting element of the first embodiment and a schematic cross-sectional view showing the nanoparticle structure side by side. Figure 2 This is a schematic energy band diagram of each layer of the light-emitting element according to the first embodiment. Figure 3 This is a flowchart for explaining an example of the method for manufacturing the light emitting element according to the first embodiment. Figure 4 This is a graph showing an example of an X-ray diffraction spectrum obtained by performing X-ray diffraction measurement on the first solution and the second solution of the first embodiment. Figure 5 It is a graph showing the relationship between the applied voltage and the light emitting luminance in the light emitting elements of the Example and the Comparative Example. Figure 6 It is a graph showing the relationship between power consumption and light emission brightness in the light emitting elements of the embodiment and the comparative example. Figure 7 It is a schematic cross-sectional view showing a light-emitting element according to the second embodiment and a schematic cross-sectional view showing a nanoparticle structure side by side. Figure 8 This is a schematic cross-sectional view of a light emitting element according to a third embodiment. Fig. 9 It is a schematic cross-sectional view of a display device according to a fourth embodiment. Fig.10 This is a schematic energy band diagram of each layer of the red light-emitting element in the fourth embodiment. DETAILED DESCRIPTION
[0013] [First embodiment] (Light Emitting Element: Overview) In this embodiment, a charge injection type light emitting element, particularly in this embodiment, a light emitting element having quantum dots as a light emitting material in a light emitting layer is used as an example for description. However, the light emitting element of this embodiment is not limited thereto, and for example, an organic EL element (OLED element) containing an organic fluorescent material or an organic phosphorescent material in the light emitting layer may also be used.
[0014] Figure 1 1 is a diagram showing a schematic cross-sectional view of a light emitting element 1 according to the present embodiment and a schematic cross-sectional view of a nanoparticle structure 20 described later. Figure 1 The schematic cross section of the light emitting element 1 is a cross section of the light emitting element 1 along the stacking direction of each layer of the light emitting element 1. Figure 1 The schematic cross-sectional view of the nanoparticle structure 20 is a cross-sectional view of the nanoparticle structure 20 passing through the center of a nanoparticle 30 which will be briefly described later.
[0015] like Figure 1 As shown, the light-emitting element 1 includes, from the bottom, an anode 10, a hole injection layer 11, a hole transport layer 12, a light-emitting layer 13, an electron transport layer 14, and a cathode 15. In addition, the light-emitting element 1 is not limited thereto, and the stacking order of each layer may be reversed from top to bottom. Specifically, the cathode 15, the electron transport layer 14, the light-emitting layer 13, the hole transport layer 12, the hole injection layer 11, and the anode 10 may be included from the bottom.
[0016] (Light-emitting element: anode and cathode) The anode 10 and the cathode 15 are electrodes containing a conductive material and are electrically connected to the hole injection layer 11 and the electron transport layer 14. By applying a voltage to at least one of the anode 10 and the cathode 15, holes h+ and electrons e- are injected from the anode 10 and the cathode 15 into the hole injection layer 11 and the electron transport layer 14, respectively.
[0017] At least one of the anode 10 and the cathode 15 is a transparent electrode that transmits visible light. As the transparent electrode, for example, ITO (indium tin oxide), IZO (indium zinc oxide), SnO2, or FTO (fluorine-doped tin oxide) can also be used. In addition, either the anode 10 or the cathode 15 can also be a reflective electrode. The reflective electrode can include a metal material with high reflectivity of visible light, and the metal material can be, for example, Al, Ag, Cu or Au alone or an alloy thereof.
[0018] When the light emitting element 1 is a top emission type in which light is extracted from the light emitting layer 13 described later to the cathode 15 side, the anode 10 may be a reflective electrode and the cathode 15 may be a transparent electrode. On the other hand, when the light emitting element 1 is a bottom emission type in which light is extracted from the light emitting layer 13 to the anode 10 side, the anode 10 may be a transparent electrode and the cathode 15 may be a reflective electrode.
[0019] (Light-emitting element: hole injection layer and hole transport layer) The hole injection layer 11 is a layer that transports holes injected from the anode 10 to the hole transport layer 12. The hole transport layer 12 is a layer that transports holes injected from the hole injection layer 11 to the light-emitting layer 13. The materials of the hole injection layer 11 and the hole transport layer 12 can use organic or inorganic materials with hole transport properties that have been used in light-emitting elements including quantum dots or organic EL light-emitting elements.
[0020] In particular, in the present embodiment, the hole injection layer 11 contains an inorganic material, and the hole transport layer 12 contains an organic material. As the inorganic material of the hole injection layer 11, MoO3, NiO, or MgNiO can be used. In addition, as the organic material of the hole transport layer 12, 4,4',4"-tri(9-carbazolyl)triphenylamine (TCTA), 4,4'-bis[N-(1-naphthyl)-N-phenyl-amino]-biphenyl (NPB), zinc phthalocyanine (ZnPC), di[4-(N,N-dimethylphenylamino)phenyl]cyclohexane (TAPC), 4,4'-bis(carbazol-9-yl)biphenyl (CBP), 2,3,6,7 ,10,11-hexacyano-1,4,5,8,9,12-hexaazaphenylene (HATCN), poly(N-vinylcarbazole) (PVK), poly(2,7-(9,9-di-n-octylfluorene)-(1,4-phenylene-((4-sec-butylphenyl)imino)-1,4-phenylene (TFB) or N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)-benzidine (Poly-TPD), etc.
[0021] In addition, in the present disclosure, "organic" or "organic material" means a substance in which carbon is the center of an atomic bond, and "inorganic" or "inorganic material" means a substance other than organic. Therefore, in the present disclosure, the so-called "inorganic" or "inorganic material" preferably means a substance in which carbon is not included in an atomic bond. In addition, carbon may be a substance that is not included in the center of an atomic bond. Moreover, it is not excluded that it means a substance that does not have a carbon chain.
[0022] Generally, among materials having hole transport properties, organic materials have higher hole transport properties than inorganic materials. On the other hand, generally speaking, among materials having hole transport properties, inorganic materials have higher resistance to foreign matter such as moisture and heat than organic materials, and have higher reliability. Therefore, the light-emitting element 1 can improve the efficiency of hole transport by having a hole injection layer 11 including an inorganic material and a hole transport layer 12 including an organic material, thereby improving the light-emitting efficiency and reliability.
[0023] However, the hole injection layer 11 may also include a composite of PEDOT (poly (3, 4-ethylenedioxythiophene)) and PSS (poly (4-styrenesulfonic acid)) called PEDOT:PSS, or an organic material such as HATCN exemplified above. In addition, the hole transport layer 12 may also include metal oxides such as NiO, MgNiO, LaNiO3, CuO, Cu2O, MoO3, or inorganic materials such as materials having CN groups, SCN groups, or SeCN groups bonded to metals, such as CuSCN.
[0024] When the hole injection layer 11 or the hole transport layer 12 contains an inorganic material, the hole injection layer 11 or the hole transport layer 12 may also have a SAM (Self Assemble Monolayer) film at the interface with other layers. In this case, since the hole injection layer 11 or the hole transport layer 12 efficiently transports holes via the SM film, the driving voltage of the light-emitting element 1 is reduced.
[0025] (Light-emitting element: electron transport layer) The electron transport layer 14 is a layer that transports electrons injected from the cathode 15 to the light-emitting layer 13. In the present embodiment, the electron transport layer 14 is an intermediate layer containing an inorganic material having electron transport properties, and in particular, a nanoparticle structure 20 containing an inorganic material. In the present disclosure, the layer between the light-emitting layer 13 and the cathode 15 is referred to as an intermediate layer. In addition, the following description is made by taking the case where an electron transport layer is provided as an intermediate layer as an example, but the present disclosure is not limited to this. For example, the light-emitting element may have an electron injection layer and an electron transport layer as an intermediate layer, or may have an electron injection layer as an intermediate layer of the present disclosure.
[0026] Reference Figure 1 The schematic cross-sectional view of the nanoparticle structure 20 of the electron transport layer 14 is shown in detail. The nanoparticle structure 20 has at least one nanoparticle 30 (first material portion, first portion) composed of a first material described later, and a second material portion 31 (second portion) formed on at least a portion of a surface 30S of the nanoparticle 30 and composed of a second material described later.
[0027] In the present disclosure, "nanoparticle" refers to a point (particle) consisting of particles whose maximum width is less than 1000nm. The shape of the nanoparticle is not particularly limited as long as it satisfies the scope of the above-mentioned maximum width, and is not limited to a spherical three-dimensional shape (circular cross-sectional shape). For example, it can be a polygonal cross-sectional shape, a rod-shaped three-dimensional shape, a branch-shaped three-dimensional shape, a three-dimensional shape with concave-convex on the surface, or a combination of these shapes.
[0028] In addition, the electron transport layer 14 may also have an organic ligand coordinated to the outermost surface of the nanoparticle structure 20. In addition, in order to improve the dispersibility and film-forming properties of the nanoparticles 30, the electron transport layer 14 may further have an organic substance such as a dispersant and a thickener. As an example of such an organic substance, oleic acid, oleylamine, 2-aminoethanol, etc. can be cited.
[0029] The first material contains a metal oxide having electron transport properties, specifically, contains at least one of zinc oxide, magnesium zinc oxide, lithium zinc oxide, titanium oxide, and strontium titanium oxide. Zinc oxide, for example, includes ZnO. Magnesium zinc oxide, for example, includes MgZnO. Lithium zinc oxide, for example, includes LiZnO. Titanium oxide, for example, includes TiO2. Strontium titanium oxide, for example, includes SrTiO3 (strontium titanate).
[0030] The second material is an inorganic material having a lower electron transport capability than the first material. In this embodiment, "electron transport capability" refers to the ability to transport electrons injected from other layers. For example, the second material has a lower electron mobility than the first material, in other words, the ability to transport electrons injected from other layers is low.
[0031] Specifically, the second material includes at least one of the group consisting of magnesium oxide, zirconium oxide, aluminum oxide, yttrium oxide, silicon oxide, zinc sulfide, magnesium zinc sulfide, and strontium sulfide. Magnesium oxide includes, for example, MgO. Zirconium oxide includes, for example, ZrO2 (zirconium oxide). Aluminum oxide includes, for example, Al2O3 (aluminum oxide). Yttrium oxide includes, for example, Y2O3. Silicon oxide includes, for example, SiO2 (silicon dioxide) or SiO (silicon monoxide). Zinc sulfide includes, for example, ZnS. Magnesium zinc sulfide includes, for example, MgZnS. Strontium sulfide includes, for example, SrS. In addition, the composition expressed as a chemical formula in the present disclosure is preferably stoichiometric. However, situations other than stoichiometric are not excluded.
[0032] The analysis of the structure of the electron transport layer 14 can be performed, for example, by dividing the electron transport layer 14 in the stacking direction of the light-emitting element 1 into thin slices, and observing the thin slices by TEM (Transmission Electron Microscope) or the like. In particular, elemental analysis of the electron transport layer 14 can be performed by performing elemental analysis on the thin slices using EDX (Energy Dispersive X-ray Spectroscopy) or EELS (Electron Energy-Loss Spectroscopy). EELS is used when EDX cannot be measured.
[0033] For example, in the EDX or EELS of the above-mentioned thin film, when a spectrum having a peak specific to the first material or the second material is obtained from a specific position, it can also be judged that a component composed of the first material or the second material exists at the position. Thus, for example, it is confirmed that: in the thin film, at least a portion of the component containing the second material is formed on the periphery of the component containing the first material. In this case, the electron transport layer 14 can be judged to include a nanoparticle structure 20, and the nanoparticle structure 20 has nanoparticles 30 composed of the first material, and a second material portion 31 formed on the surface 30S of the nanoparticle 30. In addition, here, "the periphery of the component" refers to an area within a range of 2nm starting from the end of the component. That is, in order to confirm a nanoparticle structure 20 having a nanoparticle 30 composed of a first material and a second material portion 31 formed on at least a portion of the surface 30S of the nanoparticle 30, it can be confirmed that at least a portion of the component containing the second material is formed in an area within a range of 2nm starting from at least a portion of the end of the component containing the first material.
[0034] The thickness of the second material portion 31, in other words, the thickness from the surface 30S of the nanoparticle 30 to the outermost periphery of the nanoparticle structure 20 can be greater than 0.4nm and less than 2.0nm, or can be greater than 0.4nm and less than 1.0nm. If the thickness of the second material portion 31 is greater than 0.4nm, the second material portion 31 can be more reliably formed on the surface 30S of the nanoparticle 30 by the method described later. In addition, if the thickness of the second material portion 31 is less than 2.0nm, carriers can be moved by tunnel conduction, and if it is less than 1.0nm, the effect of reducing the driving voltage (power consumption) of the light-emitting element 1 described later can be obtained more efficiently. The thickness of the second material portion 31 can also be measured by elemental analysis using the above-mentioned EDX or EELS.
[0035] (Light-emitting element: light-emitting layer) Return to reference Figure 1 A schematic cross-sectional view of a light-emitting element 1 is shown, wherein the light-emitting layer 13 has, for example, quantum dots 40 as a light-emitting material. In the present disclosure, "quantum dots" refer to dots composed of nanoparticles having a maximum width of 100 nm or less. The shape of the quantum dots is not particularly limited as long as it satisfies the range of the above-mentioned maximum width, and is not limited to a spherical three-dimensional shape (circular cross-sectional shape). For example, it may be a polygonal cross-sectional shape, a rod-shaped three-dimensional shape, a branch-shaped three-dimensional shape, a three-dimensional shape with concave and convex surfaces, or a combination of these shapes.
[0036] The quantum dot 40 may also be a quantum dot of a core / shell structure having a core and a shell formed around the core. In this case, the electrons and holes injected into the light-emitting layer 13 recombine in the core of the quantum dot 40, thereby obtaining light from the quantum dot 40. The light emission from the quantum dot 40 has a narrow spectrum due to the quantum confinement effect, so that light emission with a deeper chromaticity can be obtained. The shell may also have the function of suppressing the generation of defects or dangling bonds in the core, and reducing the recombination of carriers that have undergone a deactivation process. However, the quantum dot 40 is not limited to the above, and may also have various structures known in the past. In addition, the light-emitting layer 13 may also have an organic ligand coordinated to the outermost surface of the quantum dot 40.
[0037] In particular, in the light-emitting layer 13 of the present embodiment, the ratio of cadmium atoms in all atoms of the quantum dots 40 as the light-emitting material is less than 0.01 wt%. In other words, the ratio of cadmium atoms in the quantum dots 40 is less than 0.01 wt%, or the quantum dots 40 do not have cadmium atoms. Therefore, in the light-emitting element 1, the ratio of cadmium atoms in the quantum dots 40 is less than the maximum allowable concentration of the RoHS (Restriction of the Use of Certain Hazardous Substances in Electrical Equipment) directive, and the disposal or recycling of the product including the light-emitting element 1 can be performed more simply.
[0038] However, the quantum dot 40 is not limited to the above, and may be composed of various materials known in the past. For example, the quantum dot 40 may also have a core / shell structure such as InP / ZnS, ZnSe / ZnS, or CIGS / ZnS. In addition, the quantum dot may also have a multilayer shell containing multiple materials different from each other.
[0039] The particle size of the quantum dot 40 is about 1 to 100 nm. The wavelength of light emitted from the quantum dot 40 can be controlled by the particle size. In particular, when the quantum dot 40 has a core / shell structure, the wavelength of light emitted from the quantum dot 40 can be controlled by controlling the particle size of the core. Therefore, by controlling the particle size of the core of the quantum dot 40, the wavelength of light emitted by the light-emitting element 1 can be controlled.
[0040] (Light-emitting element: Effect of the electron transport layer) Reference Figure 2 , the effect of the electron transport layer 14 is described in detail. Figure 2 is an energy band diagram of each layer of the light emitting element 1 of this embodiment. Figure 2 In , the Fermi levels of the anode 10 and the cathode 15 are represented. Figure 2, the band gaps of the hole injection layer 11 , the hole transport layer 12 , the light emitting layer 13 , and the electron transport layer 14 are indicated.
[0041] In particular, Figure 2 In FIG. 1 , for the light-emitting layer 13, the band gap of the quantum dot 40 is shown. Figure 2 In FIG. 1 , for the electron transport layer 14 , the band gaps of the nanoparticles 30 made of the first material and the second material portion 31 made of the second material are shown. Figure 2 The energy band diagram shows the energy levels of each layer based on the vacuum energy level Evac.
[0042] Reference Figure 2 , the potential barrier for injecting electrons from the electron transport layer 14 into the light emitting layer 13 is studied. Here, the electron affinity of the light emitting layer 13 is set to EA1, the electron affinity of the nanoparticles 30 of the electron transport layer 14 is set to EA2, and the electron affinity of the second material part 31 is set to EA3. Figure 2 As shown, in this embodiment, the electron affinity EA1 of the light-emitting layer 13 is smaller than the electron affinity EA2 of the nanoparticles 30 of the electron transport layer 14, and on the other hand, is larger than the electron affinity EA3 of the second material portion 31. However, the electron affinity EA3 of the second material portion 31 is assumed to be a case where various materials are used, and sometimes the electron affinity EA1 of the light-emitting layer 13 is smaller than the electron affinity EA3 of the second material portion 31. The following describes a case where the electron affinity EA1 of the light-emitting layer 13 is smaller than the electron affinity EA3 of the second material portion 31.
[0043] In addition, the electron affinity EA1 of the light-emitting layer 13 is represented by the absolute value of the energy difference between the vacuum energy level Evac and the lower end (CBM) of the conduction band of the light-emitting layer 13. In addition, the electron affinity EA2 of the nanoparticles 30 of the electron transport layer 14 is represented by the absolute value of the energy difference between the vacuum energy level Evac and the CBM of the nanoparticles 30 of the electron transport layer 14. The electron affinity EA3 of the second material portion 31 of the electron transport layer 14 is represented by the absolute value of the energy difference between the vacuum energy level Evac and the CBM of the second material portion 31 of the electron transport layer 14.
[0044] Therefore, when the electron affinity EA1 of the light emitting layer 13 is smaller than the electron affinity EA2 of the nanoparticles 30 of the electron transport layer 14 and the electron affinity EA3 of the second material portion 31, Figure 2 In the embodiment, the upper end of the band gap corresponding to the light emitting layer 13 is higher than the upper end of the band gap of the nanoparticles 30 and the second material portion 31 of the electron transport layer 14 .
[0045] In addition, the band gap of the second material portion 31 is greater than the band gap of the nanoparticle 30. In other words, the band gap of the second material is greater than the band gap of the first material, and the electron affinity of the second material is less than the electron affinity of the first material. Therefore, the difference between the electron affinity EA1 of the light-emitting layer 13 and the electron affinity EA3 of the second material portion 31 is less than the difference between the electron affinity EA1 of the light-emitting layer 13 and the electron affinity EA2 of the nanoparticle 30. Figure 2 As shown, this is equivalent to the case where the difference between the upper end of the band gap of the second material part 31 and the upper end of the band gap of the light-emitting layer 13 is smaller than the difference between the upper end of the band gap of the nanoparticle 30 and the upper end of the band gap of the light-emitting layer 13 .
[0046] Typically, in a charge injection type light-emitting element, the height of the potential barrier when injecting electrons from a first layer into a second layer adjacent to the first layer is represented by the energy difference between the CBM of the first layer and the CBM of the second layer, which is equivalent to the energy obtained by subtracting the electron affinity of the second layer from the electron affinity of the first layer.
[0047] like Figure 2 As shown, when the second material portion 31 is provided on the surface of the nanoparticle 30, the barrier for electron injection from the second material portion 31 to the light-emitting layer 13 is smaller than the barrier for electron injection from the nanoparticle 30 to the light-emitting layer 13. Therefore, the electron transport layer 14 has the nanoparticle 30 and the second material portion 31, thereby reducing the barrier for electron injection from the electron transport layer 14 to the light-emitting layer 13. Therefore, the light-emitting element 1 can achieve electron transport from the cathode 15 to the light-emitting layer 13 at a lower applied voltage through the electron transport layer 14, thereby reducing the driving voltage of the light-emitting element 1.
[0048] Generally, the electron injectability is improved due to the reduction of the barrier to electron injection. However, as described above, the second material has a lower electron transport capability than the first material. Therefore, the efficiency of electron transport from the cathode 15 to the light-emitting layer 13 via the electron transport layer 14 is lower than that of the electron transport layer 14 having only the nanoparticles 30. Therefore, the light-emitting element 1 can reduce the excess of electrons in the light-emitting layer 13 by reducing the electron density in the light-emitting layer 13, thereby improving the carrier balance of the light-emitting layer 13. Therefore, according to this embodiment, by using a second material having a lower electron transport capability than the first material, it is possible to simultaneously achieve a reduction in driving voltage and suppression of electron injection.
[0049] In summary, the light-emitting element 1 can reduce the driving voltage through the electron transport layer 14 and improve the carrier balance of the light-emitting layer 13 .
[0050] (Method for manufacturing a light-emitting element: until formation of a light-emitting layer) Reference Figure 3 A method for manufacturing the light emitting element 1 of this embodiment will be described. Figure 3This is a flowchart for explaining an example of a method for manufacturing the light emitting element 1 .
[0051] In the manufacturing method of the light emitting element 1 of the present embodiment, first, the anode 10 is formed (step S1). The anode 10 can also be formed by forming a conductive material on a substrate by, for example, sputtering. Specifically, for example, a thin film of ITO having a film thickness of 30 nm and a size of 2 mm×10 mm can be formed on a substrate by sputtering to form the anode 10.
[0052] Next, a hole injection layer 11 is formed (step S2). The hole injection layer 11 can be formed on the anode 10 by a coating formation method such as a spin coating method using a colloidal solution, or can also be formed by a vacuum evaporation method or a sputtering method. Specifically, for example, nickel oxide with a particle size of 10 nm can also be applied to the anode 10 by spin coating and dried to form a film. Furthermore, the hole injection layer 11 can also be formed by contacting a solution dissolved in ethanol with the film in a manner of 0.01M MeO-2PACz for more than 5 seconds and drying.
[0053] Next, the hole transport layer 12 is formed (step S3). The hole transport layer 12 can be formed on the hole injection layer 11 by a coating method such as a spin coating method using a colloidal solution, or can also be formed by a vacuum evaporation method or a sputtering method. Specifically, for example, a solution obtained by dissolving 8 mg of Poly-TPD in 1 ml of chlorobenzene can be applied to the hole injection layer 11 by a spin coating method and dried.
[0054] Next, the light-emitting layer 13 is formed (step S4). In the case where the light-emitting layer 13 has the quantum dots 40 as described above, the light-emitting layer 13 can also be formed on the hole transport layer 12 by, for example, a coating formation method such as a spin coating method using a solution in which the quantum dots 40 are dispersed. Specifically, for example, 0.1 ml of a solution having a core / shell structure of InP / ZnS and in which the quantum dots 40 emitting red light are dispersed can be coated on the hole transport layer 12 by a spin coating method, and then dried to form the light-emitting layer 13. The thickness of the light-emitting layer 13 formed as described above can also be 15 nm.
[0055] In the present disclosure, red light is light having a central wavelength in a wavelength range of more than 600 nm and less than 780 nm. In the case where the light emitting layer 13 has an organic light emitting material instead of the quantum dots 40, the light emitting layer 13 may be formed by vacuum deposition or the like.
[0056] (Method for manufacturing a light-emitting element: solution synthesis) In the method for manufacturing the light-emitting element 1, the electron transport layer 14 is formed after the light-emitting layer 13. In this embodiment, as described later, the electron transport layer 14 is formed by a coating formation method using a solution having the nanoparticle structure 20. Here, in the method for manufacturing the light-emitting element 1, before executing the coating formation method, the solution used in the coating formation method is synthesized.
[0057] Specifically, in the method for manufacturing the light emitting element 1, a first solution containing the nanoparticles 30 is synthesized (step S5). The first solution can be synthesized by, for example, adding a precursor of the nanoparticles 30 containing a first material to a solvent such as ethanol and stirring the mixture.
[0058] More specifically, in step S5, first, a solution is prepared by dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in dimethyl sulfoxide at a molar ratio of 85:15. Then, a solution prepared by dissolving tetramethylammonium hydroxide in ethanol is added to the solution and stirred for 1 hour to prepare a first solution in which nanoparticles 30 containing zinc oxide are dispersed.
[0059] Next, a second solution is synthesized by adding the second material to the first solution (step S6). Specifically, magnesium acetate tetrahydrate is added to the first solution so as to be 30 mol% relative to the solute in the first solution to synthesize the second solution.
[0060] Then, carry out ultrasonic treatment (step S7) to the second solution.Through this ultrasonic treatment, the second solution is subjected to rapid and short-term heat treatment, and through this heat treatment, the surface 30S of the nanoparticle 30 in the second solution forms the second material.Thus, the surface 30S of the nanoparticle 30 in the second solution forms the second material portion 31 comprising the second material, in other words, synthesizes the nanoparticle structure 20 in the second solution.
[0061] Next, the second solution is cleaned (step S8). The cleaning of the second solution is performed, for example, by adding an appropriate solvent to the second solution, subjecting the second solution to a centrifugal separator, and removing the first material or the second material not contained in the nanoparticle structure 20 from the second solution. Through the above, the synthesis of the second solution used in the coating formation method of the electron transport layer 14 is completed. In addition, between step S7 and step S8, the second solution can also be left to stand for an appropriate period.
[0062] (Method for manufacturing a light-emitting element: element identification of a solution) The elements contained in the first solution and the second solution synthesized by the above method can be confirmed by element identification of each solution using XRD (X-Ray Diffraction). Figure 4 The method of element identification using XRD is described.
[0063] Figure 4 Graph showing the results of X-ray diffraction spectrum measurement of the first solution and the second solution synthesized by the above method. Figure 4 In the graph, the horizontal axis represents twice the incident angle (reflection angle) of the X-ray relative to the measurement object, that is, the measurement angle 2θ (unit: deg), and the vertical axis represents the intensity of the measured X-ray (arbitrary unit).
[0064] In this embodiment, the thin film synthesized in step S5 is subjected to X-ray diffraction spectrum measurement using XRD after the first solution is dropped onto the substrate and dried, and the X-ray diffraction spectrum is obtained. Figure 4 In addition, the thin film obtained by dropping the second solution synthesized in the above steps S5 to S8 onto the substrate and drying was subjected to X-ray diffraction spectrum measurement using XRD, and the obtained spectrum was Figure 4 In order to compare the two spectra easily, Figure 4 Sets the offset on the intensities of the two spectral data.
[0065] Here, Figure 4 In the figure, the reference of zinc oxide is indicated by a dotted line, and the reference of magnesium oxide is indicated by a single-dot chain line. In other words, when zinc oxide is contained in the sample measured by XRD, a peak is mainly confirmed at the measurement angle indicated by the dotted line in the spectrum data obtained by the measurement. In addition, when magnesium oxide is contained in the sample measured by XRD, a peak is mainly confirmed at the measurement angle indicated by the single-dot chain line in the spectrum data obtained by the measurement.
[0066] like Figure 4 As shown, in both the spectrum data D1 and the spectrum data D2, a peak indicating the presence of zinc oxide was confirmed. Therefore, it was confirmed that the first solution and the second solution synthesized by the above method contained a material having a crystalline structure of zinc oxide. On the other hand, in the spectrum data D2, although a peak P indicating the presence of magnesium oxide was confirmed near a measurement angle of 42 degrees, no peak at the same measurement angle was confirmed in the spectrum data D1. Therefore, it was confirmed that the second solution synthesized by the above method contained a material having a crystalline structure of magnesium oxide, but it was not contained in the first solution.
[0067] Furthermore, in order to identify the elements contained in the first solution and the second solution, element analysis based on ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometer) or XPS (X-ray Photo-electron Spectroscopy) or the like may be used.
[0068] For example, it is actually possible to confirm that the first solution contains Mg by performing an elemental analysis based on ICP-AES or XPS on the first solution synthesized by the above method. In this case, it is known that the first solution does not contain magnesium oxide, but has a crystalline structure of zinc oxide, and further synthesized a material containing Mg atoms. In other words, it is known that nanoparticles 30 containing magnesium zinc oxide as the first material are synthesized in the first solution. It can be seen from this that the second solution synthesized from the first solution also includes nanoparticles 30 containing magnesium zinc oxide as the first material.
[0069] As described above, it was confirmed that the first solution contained nanoparticles 30 containing magnesium zinc oxide as the first material. In addition, it was confirmed that the second solution contained nanoparticles 30 containing magnesium zinc oxide as the first material and the second material part 31 containing magnesium oxide as the second material.
[0070] (Method for manufacturing a light-emitting element: formation of an electron transport layer and a cathode) In the method for manufacturing the light emitting element 1, after step S4 and step S8 are completed, the second solution is applied on the light emitting layer 13 by spin coating or the like (step S9). Next, the applied second solution is dried to form the electron transport layer 14 having the nanoparticle structure 20 (step S10). The thickness of the electron transport layer 14 formed as described above may also be 40 nm.
[0071] Next, similarly to the anode 10, a conductive material is deposited on the electron transport layer 14 by sputtering or vacuum deposition to form the cathode 15 (step S11). Specifically, for example, a 50 nm thick Ag thin film can be formed on the electron transport layer 14 by vacuum deposition.
[0072] (Summary of the First Embodiment) The light emitting element 1 of the present embodiment has an electron transport layer 14 as an intermediate layer including a nanoparticle structure 20. The nanoparticle structure 20 includes: a nanoparticle 30 composed of a first material including a metal oxide; and a second material portion 31 formed on at least a portion of a surface 30S of the nanoparticle 30 and composed of an inorganic second material having a lower electron transport capability than the first material.
[0073] Therefore, based on the above reasons, the light-emitting element 1 can improve the carrier balance of the light-emitting layer 13 while reducing the driving voltage through the electron transport layer 14. In addition, compared with the case where the light-emitting element 1 has a stacked structure of a layer composed of a first material and a layer composed of a second material as an electron transport layer, the overall thickness of the light-emitting element 1 is reduced and the driving voltage is reduced. Moreover, compared with the case where the light-emitting element 1 has an electron transport layer of nanoparticles composed of a first material and nanoparticles composed of a second material, conduction from the cathode 15 to the light-emitting layer 13 is more reliably achieved through the electron transport layer 14, reducing the driving voltage.
[0074] The electron transport layer 14 of the present embodiment is formed by coating the second solution. In the present embodiment, the second material is added to the first solution containing the nanoparticles 30, and then ultrasonic treatment is performed to synthesize the second solution, which contains a nanoparticle structure 20 having a second material portion 31 formed on the surface of at least a portion of the nanoparticles 30. In other words, in the present embodiment, the nanoparticle structure 20 is synthesized in a state where the first material and the second material are always in the solvent. Therefore, in the present embodiment, the nanoparticle structure 20 can be formed while ensuring the dispersibility of the nanoparticles 30 and the second material in the second solution.
[0075] For example, due to the different dispersibility of the first material and the second material, it is sometimes difficult to form an electron transport layer containing both nanoparticles composed of the first material and nanoparticles composed of the second material from a solution in which nanoparticles composed of the first material and nanoparticles composed of the second material are mixed. According to the method for forming the electron transport layer 14 of the present embodiment, since the nanoparticle structure 20 is synthesized while ensuring the dispersibility of each material in the second solution, the nanoparticle structure 20 can be easily synthesized even when there is a difference in the dispersibility of the first material and the second material.
[0076] Therefore, according to the method for manufacturing the light-emitting element 1 of the present embodiment, since the degree of freedom in designing the first material and the second material is further expanded, it is possible to more easily design the electron transport layer 14 that can improve the carrier balance in the light-emitting layer 13. Therefore, the method for manufacturing the light-emitting element 1 of the present embodiment can provide the light-emitting element 1 that can improve the carrier balance in the light-emitting layer 13.
[0077] Furthermore, according to the method for manufacturing the light-emitting element 1 of the present embodiment, the electron transport layer 14 can be formed without a process such as a sputtering method that can cause deactivation of the light-emitting material containing the quantum dots 40 of the light-emitting layer 13. In addition, according to the above method, the nanoparticle structure 20 can be synthesized by ultrasonically treating the second solution and rapidly and briefly heating the second solution, thereby reducing the damage caused by heating of the materials of the second solution. Therefore, the method for manufacturing the light-emitting element 1 of the present embodiment can reduce the damage caused to the light-emitting layer 13 and the electron transport layer 14, and provide a light-emitting element 1 with higher reliability.
[0078] In this embodiment, in the nanoparticle structure 20, as Figure 1 As shown in the figure, the second material portion 31 is formed on the entire surface 30S of the nanoparticle 30 , but the invention is not limited thereto. For example, the second material portion 31 may be formed on at least a portion of the surface 30S of the nanoparticle 30 .
[0079] For example, in the present embodiment, in the cross section of the nanoparticle 30, the second material portion 31 may also cover more than 10% of the periphery of the nanoparticle 30. For example, by performing elemental analysis on the thin slice after dividing the electron transport layer 14 along the stacking direction of the light-emitting element 1, it can be confirmed that the second material portion 31 covers more than 10% of the periphery of the nanoparticle 30 at any position. In this case, the uniformity of the particle size of the nanoparticle structure 20 is improved, the unevenness of the film thickness of the electron transport layer 14 is reduced, and the stability of the path for transmitting electrons in the electron transport layer 14 is improved. In addition, in the above case, the second material portion 31 more reliably hinders the electron transport, so that the excess of electrons in the light-emitting layer 13 can be further reduced. As a result, the electron transport layer 14 further achieves a reduction in the excess of electrons in the light-emitting layer 13 and a reduction in the driving voltage of the light-emitting element 1. In addition, the second material portion 31 more preferably covers at least 1 / 6 of the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30. The “ratio of covering the outer periphery” in the present disclosure refers to the ratio of the outer periphery in a cross section of the nanoparticle 30 , and does not refer to the ratio of the three-dimensional surface area of the nanoparticle 30 .
[0080] In addition, depending on the various conditions of the manufacturing method of the above-mentioned light emitting element 1, in step S5, sometimes nanoparticles 30 with low uniformity are obtained. In this case, before step S6, a shell layer consisting of the same first material as the first material of the nanoparticle 30 may be formed on the surface of the nanoparticle 30. Thus, the uniformity of the nanoparticle 30 is improved, and then the uniformity of the nanoparticle structure 20 is improved.
[0081] As described above, the quantum dot 40 of this embodiment may also contain cadmium. Generally, high characteristics are obtained by using a light-emitting material containing cadmium. However, by using a light-emitting material that does not use cadmium, safety can be improved.
[0082] As a quantum dot 40 that does not contain cadmium, for example, a quantum dot having a core / shell structure with InP / ZnS, InP / ZnSe, etc. can be used. In this case, a mixed crystal layer formed by mutual substitution of indium of InP in the core of the quantum dot 40 and zinc of ZnS or ZnSe in the quantum dot 40 is sometimes formed between the core and shell of the quantum dot 40.
[0083] In the mixed crystal layer, the core and the shell form a pn junction. Therefore, in the injection of carriers from the shell of the quantum dot 40 to the core, the mixed crystal layer does not serve as a barrier to the injection of electrons, but can serve as a barrier to the injection of holes. Therefore, in the light-emitting element 1 having the light-emitting layer 13 including the quantum dot 40, there is a situation where the excess of electrons in the light-emitting layer 13 worsens.
[0084] The light emitting element 1 of this embodiment can be configured as follows, comprising: a light emitting layer 13 including quantum dots 40 not containing cadmium as a light emitting material; and an electron transport layer 14 that can reduce the excess of electrons in the light emitting layer 13. With this configuration, the light emitting element 1 can further reduce the excess of electrons in the light emitting layer 13, reduce the driving voltage, and improve safety, making it easier to handle products such as waste disposal or recycling of the light emitting element 1.
[0085] As described above, the light-emitting element 1 of the present embodiment may also include a hole injection layer 11 containing an inorganic material. Generally speaking, when a light-emitting element includes a hole injection layer containing an inorganic material, the reliability is improved compared to the case where the light-emitting element includes a hole injection layer containing an organic material, but the efficiency of hole transport in the hole injection layer is reduced, so that the excess of electrons in the light-emitting layer may sometimes further deteriorate.
[0086] However, the light-emitting element 1 of this embodiment includes an electron transport layer 14 that can reduce the excess of electrons in the light-emitting layer 13. Therefore, according to this embodiment, even if the light-emitting element 1 includes the hole injection layer 11 containing an inorganic material as described above, by including such an electron transport layer 14, the excess of electrons in the light-emitting layer 13 can be reduced, and the reliability of the light-emitting element 1 can be further improved.
[0087] Furthermore, as described above, the light-emitting element 1 of the present embodiment may also include a hole transport layer 12 containing an organic material. In this case, compared with the case where the light-emitting element 1 includes a hole transport layer 12 containing an inorganic material, the efficiency of hole transport in the hole transport layer 12 is improved, and therefore, the excess of electrons in the light-emitting layer 13 can be further reduced. For example, the light-emitting element 1 may also include a hole injection layer 11 containing an inorganic material and a hole transport layer 12 containing an organic material. In this case, reliability is ensured by the hole injection layer 11, and the excess of electrons in the light-emitting layer 13 can be further reduced by the hole transport layer 12.
[0088] (Evaluation of characteristics of light-emitting elements) The characteristics of the light emitting element 1 of the present embodiment were evaluated by comparing the characteristics of the light emitting elements of the example and the comparative example. Specifically, the light emitting elements of the example 1 and the comparative example 1 described below were manufactured, and the characteristics were compared.
[0089] The light-emitting element of Example 1 is a light-emitting element manufactured according to the manufacturing method of the light-emitting element 1 of the present embodiment. Therefore, the light-emitting element of Example 1 includes a nanoparticle structure 20 in the electron transport layer 14, and the nanoparticle structure 20 has a nanoparticle 30 and a second material portion 31 formed on at least a portion of the surface 30S of the nanoparticle 30.
[0090] The light-emitting element of Comparative Example 1 is a light-emitting element manufactured by changing a part of the manufacturing method of the light-emitting element 1 of the present embodiment described above, compared with the light-emitting element of Example 1. In the manufacturing method of the light-emitting element of Comparative Example 1, steps S6 to S8 are not implemented. Furthermore, in the manufacturing method of the light-emitting element of Comparative Example 1, a first solution is applied on the light-emitting layer 13 in step S9, and the first solution is dried in step S10 to form an electron transport layer. Therefore, in the light-emitting element of Comparative Example 1, the electron transport layer contains nanoparticles 30, but does not contain the second material portion 31.
[0091] For the light emitting elements of Example 1 and Comparative Example 1, the current density was increased from 0V to 25mA / cm 2 The characteristics of each light-emitting element were measured by applying a voltage of about 100° and measuring the luminance of light emission. The luminance of each light-emitting element was measured using a spectrophotometer "Photal MCPD-7000" manufactured by Otsuka Electronics Co., Ltd. In addition, the applied voltage and current density of each light-emitting element were measured using a source meter 2400 manufactured by Keighley Instruments.
[0092] Figure 5 as well as Figure 6 The graph shows the results of this measurement. Figure 5A graph showing the relationship between the applied voltage and the light emitting luminance of the light emitting elements of Example 1 and Comparative Example 1. Figure 6 This is a graph showing the relationship between power consumption and light emission brightness calculated from current density and applied voltage of the light emitting elements of Example 1 and Comparative Example 1. Figure 5 The horizontal axis of the curve graph is the applied voltage (unit: V). Figure 6 The horizontal axis of the graph is power consumption (unit: mW / cm2). Figure 5 and Figure 6 The vertical axis of the graph is the luminous brightness (unit: cd / m 2 ).
[0093] Reference Figure 5 From the curve graph, it can be seen that the light-emitting element of Example 1 emits light with a higher brightness than the light-emitting element of Comparative Example 1 when a voltage higher than about 3V is applied. Figure 6 As can be seen from the curve graph, the light-emitting element of Example 1 can achieve the same brightness with lower power consumption than the light-emitting element of Comparative Example 1. Figure 6 In the graph of , data showing that almost no brightness is obtained as data of Comparative Example 1 indicates that even if voltage is applied to the light-emitting element of Comparative Example 1, sometimes almost no light is emitted.
[0094] The above results are obtained because: the light-emitting element of Example 1 has an electron transport layer 14 containing a nanoparticle structure 20, so that the excess of electrons in the light-emitting layer 13 is reduced compared with the light-emitting element of Comparative Example 1, and the external quantum efficiency is improved. In addition, it can be considered that since the light-emitting element of Example 1 has an electron transport layer 14 containing a nanoparticle structure 20, the driving voltage of the light-emitting element required to obtain the same brightness is reduced compared with the light-emitting element of Comparative Example 1, and the overall power consumption of the light-emitting element is reduced.
[0095] In particular, the electron transport layer 14 of the light-emitting element of Example 1 includes nanoparticles 30 containing magnesium zinc oxide as a first material and a second material portion 31 containing a metal oxide as a second material. Since magnesium zinc oxide is soluble in alkali, by forming the second material portion 31 containing a metal oxide other than magnesium zinc oxide that is resistant to alkali, process resistance can be improved.
[0096] As the second material, the metal oxide having resistance to alkali may be, for example, aluminum oxide (eg, Al2O3). In addition, as described above, the composition expressed by the chemical formula in the present disclosure is preferably stoichiometric. However, this does not exclude situations other than stoichiometric.
[0097] In addition, the electron transport layer 14 of the light-emitting element of Example 1 has a second material portion 31, and the second material portion 31 contains magnesium oxide with high light transmittance as the second material. Therefore, in the case where the light-emitting element is a top emission type that extracts light from the light-emitting layer 13 to the cathode 15 side, the electron transport layer 14 of Example 1 reduces the light from the light-emitting layer 13 being absorbed by the second material portion 31 of the electron transport layer 14. Therefore, the light-emitting element of Example 1 can further improve the light extraction efficiency.
[0098] [Second embodiment] Hereinafter, for the sake of convenience, components having the same functions as those described in the previous embodiments are denoted by the same reference numerals, and their description will not be repeated.
[0099] (Variation Example of Nanoparticle Structure) Figure 7 2 is a diagram showing a schematic cross-sectional view of a light emitting element 2 of the present embodiment and a schematic cross-sectional view of a nanoparticle structure 21 described later. Figure 7 The schematic cross-sectional view of the light emitting element 2 is a diagram showing Figure 1 The cross section corresponds to the schematic cross-sectional view of the light emitting element 1. In addition, Figure 7 A schematic cross-sectional view of a nanoparticle structure 21 and Figure 1 Similar to the schematic cross-sectional view of the nanoparticle structure 20 , the cross section of the nanoparticle structure 21 passing through the center of the nanoparticle 30 is simply shown.
[0100] The light emitting element 2 of this embodiment is different from the light emitting element 1 of the first embodiment only in that it includes an electron transport layer 16 instead of the electron transport layer 14. The electron transport layer 16 is different from the electron transport layer 14 only in that it includes a nanoparticle structure 21 instead of the nanoparticle structure 20. In other words, the electron transport layer 16, like the electron transport layer 14, transmits the electrons e injected from the cathode 15 to the electron transport layer 16. - Transmitted to the light-emitting layer 13.
[0101] The nanoparticle structure 21 has a second material portion 32 formed in an island shape on the surface 30S of the nanoparticle 30. The second material portion 32 is made of the same material as the second material portion 31 of the first embodiment, in other words, a second material.
[0102] Therefore, the electron transport layer 16 is a sandwich having a nanoparticle 30 and a second material portion 32, wherein the nanoparticle 30 is composed of a first material including a metal oxide, and the second material portion 32 is located in an island shape on a portion of the surface 30S of the nanoparticle 30, and is composed of an inorganic second material having a lower electron transport ability than the first material. Therefore, the light-emitting element 2 can reduce the driving voltage through the electron transport layer 16 and improve the carrier balance of the light-emitting layer 13 for the same reasons as those described in the first embodiment.
[0103] In addition, the analysis of the structure of the electron transport layer 16 can also be performed by the same method as the analysis of the structure of the electron transport layer 14 described above. Specifically, the electron transport layer 16 can be divided into thin slices in the stacking direction of the light-emitting element 2, and the thin slices can be observed by TEM or the like, and elemental analysis using EDX or EELS can be performed to perform elemental analysis of the electron transport layer 16. In addition, in this embodiment, EELS is also used when measurement with EDX is not possible.
[0104] For example, in the above-mentioned thin film, it can be confirmed that at least a part of the periphery of the component containing the first material and at least a part of the component containing the second material are formed at multiple positions. In this case, it can be determined that the electron transport layer 16 includes a nanoparticle structure 21, which has a nanoparticle 30 composed of a first material, and a second material portion 32 located in an island shape on the surface 30S of the nanoparticle 30. In this way, the second material portion 32 is located in an island shape on the surface 30S of the nanoparticle 30, which means that the second material portion 32 is located in an island shape on the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30. In this way, the electron transport layer 16 has a structure of the nanoparticle structure 21, which can be confirmed by, for example, elemental analysis of the above-mentioned thin film. In addition, in this case, the "periphery of the component" refers to an area within a range of 2nm from the end of the component. That is, when confirming a nanoparticle structure 21 having a nanoparticle 30 composed of a first material and a second material portion 32 arranged in an island shape on the surface 30S of the nanoparticle 30, it can be confirmed that at least a portion of the component containing the second material is formed in a portion of an area within a 2nm range starting from at least a portion of the end of the component containing the first material, and at multiple positions.
[0105] The thickness of the second material portion 32, in other words, the thickness from the surface 30S of the nanoparticle 30 to the outermost periphery of the nanoparticle structure 21 can be greater than 0.4nm and less than 2.0nm, or can be greater than 0.4nm and less than 1.0nm. If the thickness of the second material portion 32 is greater than 0.4nm, the second material portion 32 can be more reliably formed on the surface 30S of the nanoparticle 30 by the method described later. In addition, if the thickness of the second material portion 32 is less than 2.0nm, carriers can be moved by tunnel conduction, and if it is less than 1.0nm, the effect of reducing the driving voltage (power consumption) of the light-emitting element 2 can be obtained more efficiently. The thickness of the second material portion 32 can be measured by elemental analysis using the above-mentioned EDX or EELS, etc.
[0106] In addition, the second material portion 32, like the second material portion 31, may also cover more than 10% of the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30. For example, it is also possible to confirm that the second material portion 32 covers more than 10% of the periphery of the nanoparticle 30 at any position by performing elemental analysis on the thin slice obtained by dividing the electron transport layer 14 along the stacking direction of the light-emitting element 1.
[0107] In addition, the nanoparticle structure 21 may have a structure in which the second material portion 32 covers less than 90% of the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30. This structure can be confirmed, for example, by elemental analysis of the above-mentioned thin sheet to confirm that the second material portion 32 covers less than 90% of the periphery of the nanoparticle 30 at any position.
[0108] According to the present embodiment, as described above, in the cross section of the nanoparticle 30, the second material portion 32 is located in the outer periphery of the nanoparticle 30 in an island shape, so that the effective particle size of the nanoparticle structure 21 can be reduced compared to the case where the outer periphery of the nanoparticle 30 is entirely covered with the second material portion 32. Therefore, according to the present embodiment, the increase in the particle size of the nanoparticle structure in the electron transport layer 16 can be reduced. Therefore, in the present embodiment, by increasing the concentration of the nanoparticle structure 21 in the electron transport layer 16, the efficiency of electron transport is improved, so that the applied voltage of the light-emitting element 2 can be further reduced.
[0109] The light emitting element 2 can control the degree of obstruction of the electron transport by the second material portion 32 by appropriately changing the conditions in the above-mentioned manufacturing method and changing the ratio of the second material portion 32 covering the outer periphery of the nanoparticle 30 in the cross section of the nanoparticle 30. Therefore, the light emitting element 2 can more easily reduce the excess of electrons in the light emitting layer 13 and reduce the applied voltage.
[0110] The light emitting element 2 of this embodiment can also be manufactured by changing a part of the manufacturing method of the light emitting element 1 of the first embodiment. For example, in the manufacturing method of the light emitting element 2, the concentration or type of the second material added to the first solution in step S6 of the manufacturing method of the light emitting element 1, or the conditions of the ultrasonic treatment in step S7, etc. can also be appropriately changed.
[0111] Therefore, in the method for manufacturing the light-emitting element 2 of the present embodiment, as described in the first embodiment, the nanoparticle structure 20 is synthesized while ensuring the dispersibility of each material in the second solution. Therefore, in the present embodiment, even when there is a difference in dispersibility between the first material and the second material, the nanoparticle structure 20 can be easily synthesized. Therefore, according to the method for manufacturing the light-emitting element 2 of the present embodiment, for the same reasons as described in the first embodiment, a light-emitting element 2 capable of improving the carrier balance of the light-emitting layer 13 can be provided.
[0112] [Third Embodiment] (Light-emitting element without hole injection layer) Figure 8 : is a schematic cross-sectional view of the light emitting element 3 of this embodiment. Figure 8 The schematic cross-sectional view of the light emitting element 3 is a diagram showing Figure 1 The cross section corresponds to the schematic cross-sectional view of the light-emitting element 1.
[0113] The light emitting element 3 of this embodiment differs from the light emitting element 1 of the first embodiment in that it does not include the hole injection layer 11. In other words, in this embodiment, holes from the anode 10 are injected into the hole transport layer 12 and transported to the light emitting layer 13 via the hole transport layer 12.
[0114] According to the light-emitting element 3 of this embodiment, the electron transport layer 14 having the nanoparticle structure 20 is provided in the same manner as the light-emitting element 1. Therefore, the light-emitting element 3 of this embodiment can also reduce the driving voltage through the electron transport layer 14 for the same reason as the above-mentioned reason, and improve the carrier balance of the light-emitting layer 13. Moreover, the light-emitting element 3 of this embodiment does not include the hole injection layer 11 compared with the light-emitting element 1 or the light-emitting element 2. Therefore, the light-emitting element 3 can further reduce the thickness between the electrodes, and thus can further reduce the driving voltage.
[0115] In this embodiment, the hole transport layer 12 may contain the above-mentioned inorganic material having hole transport properties. In this way, the light-emitting element 3 of this embodiment can adopt a structure having a hole transport layer 12 containing an inorganic material and an electron transport layer 14 capable of reducing the excess of electrons in the light-emitting layer 13. With this structure, the light-emitting element 3 can further reduce the excess of electrons in the light-emitting layer 13 for the same reason as above, and further improve the reliability of the light-emitting element 1.
[0116] The light-emitting element 3 of this embodiment can be manufactured by omitting only step S2 in the manufacturing method of the light-emitting element 1 described above. In other words, in this embodiment, the hole transport layer 12 can also be formed on the anode 10. Therefore, according to the manufacturing method of the light-emitting element 3 of this embodiment, for the same reasons as those described in the above embodiments, the light-emitting element 2 capable of improving the carrier balance of the light-emitting layer 13 can be provided.
[0117] [Fourth Embodiment] (Display Device) In other embodiments of the present disclosure, a display device including the light emitting element 1 will be described. Fig. 9 It is a schematic cross-sectional view of a display device 50 according to this embodiment.
[0118] The display device 50 of this embodiment is a display device that has a plurality of light-emitting elements in each of a plurality of sub-pixels, and displays by driving each light-emitting element separately. As described later, the display device 50 includes a plurality of red light-emitting elements 1R that emit red light, a plurality of green light-emitting elements 1G that emit green light, and a plurality of blue light-emitting elements 1B that emit blue light. Fig. 9 , a cross section of the display device 50 passing through each layer of a red light emitting element 1R, a green light emitting element 1G, and a blue light emitting element 1B in the stacking direction of each light emitting element of the display device 50 is shown.
[0119] The red light-emitting element 1R includes, from the bottom, an anode 10R, a hole injection layer 11R, a hole transport layer 12R, a red light-emitting layer 13R, an electron transport layer 14R, and a cathode 15. The green light-emitting element 1G includes, from the bottom, an anode 10G, a hole injection layer 11G, a hole transport layer 12G, a green light-emitting layer 13G, an electron transport layer 14G, and a cathode 15. The blue light-emitting element 1B includes, from the bottom, an anode 10B, a hole injection layer 11B, a hole transport layer 12B, a blue light-emitting layer 13B, an electron transport layer 14B, and a cathode 15.
[0120] At least one of the red light emitting element 1R, the green light emitting element 1G, and the blue light emitting element 1B may have the same structure as the light emitting element 1 of the first embodiment except for the emission color of each light emitting layer and the structure of each electron transport layer. In addition, the red light emitting element 1R, the green light emitting element 1G, and the blue light emitting element 1B may have a common cathode 15. Fig. 9 In the description, as an example, a case where the red light-emitting element 1R, the green light-emitting element 1G, and the blue light-emitting element 1B have the same configuration except for the emission color of each light-emitting layer and the configuration of each electron transport layer is taken as an example.
[0121] Specifically, the red light-emitting layer 13R of the red light-emitting element 1R has a red quantum dot 40R that emits red light. The green light-emitting layer 13G of the green light-emitting element 1G has a green quantum dot 40G that emits green light. The blue light-emitting layer 13B of the blue light-emitting element 1B has a blue quantum dot 40B that emits blue light. The red quantum dot 40R, the green quantum dot 40G, and the blue quantum dot 40B may have the same structure as the quantum dot 40 except for the luminescent color. The luminescent color of each quantum dot may also be changed by changing the particle size of the quantum dot.
[0122] In addition, as described above, red light refers to light having a luminous center wavelength in a band exceeding 600nm and below 780nm. In addition, green light, for example, refers to light having a luminous center wavelength in a band exceeding 500nm and below 600nm. And, blue light, for example, refers to light having a luminous center wavelength in a band exceeding 400nm and below 500nm.
[0123] also, Fig. 9 The red light-emitting element 1R, the green light-emitting element 1G, and the blue light-emitting element 1B shown have nanoparticle structures on the electron transport layer, respectively, and the structure has the structure described in the first embodiment. The electron transport layer 14R of the red light-emitting element 1R has a nanoparticle structure 20R. The electron transport layer 14G of the green light-emitting element 1G has a nanoparticle structure 20G. The electron transport layer 14B of the blue light-emitting element 1B has a nanoparticle structure 20B. In addition, the nanoparticle structure 20R, the nanoparticle structure 20G, and the nanoparticle structure 20B may also have the same structure as the nanoparticle structure 20 of the first embodiment, except for the proportion of the second material part 32 covering the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30 or the thickness of the second material part 31.
[0124] For any two of the red light-emitting element 1R, the green light-emitting element 1G, and the blue light-emitting element 1B, the light-emitting element with a shorter light-emitting wavelength is set as a short-wavelength element, and the light-emitting element with a longer light-emitting wavelength is set as a long-wavelength element. In this case, in the present embodiment, in the long-wavelength element, the ratio of the cross-sectional area of the second material in the electron transport layer of each light-emitting element to the cross-sectional area of the first material is smaller than that of the short-wavelength element. In this way, as described below Fig.10 As described in detail in the description of , the carrier balance can be adjusted and the driving voltage (power consumption) of the light-emitting element can be further reduced.
[0125] For example, the ratio of the cross-sectional area of the second material in the electron transport layer 14R to the cross-sectional area of the first material is smaller than the ratio of the cross-sectional area of the second material in the electron transport layer 14G to the cross-sectional area of the first material. Alternatively, the ratio of the cross-sectional area of the second material in the electron transport layer 14G to the cross-sectional area of the first material is smaller than the ratio of the cross-sectional area of the second material in the electron transport layer 14B to the cross-sectional area of the first material. Alternatively, the ratio of the cross-sectional area of the second material in the electron transport layer 14R to the cross-sectional area of the first material is smaller than the ratio of the cross-sectional area of the second material in the electron transport layer 14B to the cross-sectional area of the first material.
[0126] In this embodiment, the ratio of the cross-sectional area of the second material of the electron transport layer of each light-emitting element to the cross-sectional area of the first material can be changed by changing the ratio of the second material portion 32 covering the periphery of the nanoparticle 30 in the cross section of the nanoparticle 30 of each electron transport layer. In addition, the ratio of the cross-sectional area of the second material in the electron transport layer of each light-emitting element to the cross-sectional area of the first material can also be changed by changing the thickness of the second material portion 31 in each electron transport layer. For example, compared with the short-wavelength element, in the long-wavelength element, the ratio of the second material portion 31 formed in the surface 30S of the nanoparticle 30 can be reduced, or the thickness of the second material portion 31 can be reduced.
[0127] The display device 50 includes a substrate 60. A plurality of red sub-pixels RP, a plurality of green sub-pixels GP, and a plurality of blue sub-pixels BP are formed on the substrate 60. A plurality of light-emitting elements are formed on the substrate 60, and in particular, a red light-emitting element 1R is formed on each red sub-pixel RP, a green light-emitting element 1G is formed on each green sub-pixel GP, and a blue light-emitting element 1B is formed on each blue sub-pixel BP.
[0128] The red light emitting element 1R, the green light emitting element 1G, and the blue light emitting element 1B are arranged so that each anode is formed on the substrate 60 side. Therefore, on the substrate 60, the anode of each light emitting element is formed in an island shape for each sub-pixel, and the cathode 15 is formed in common for a plurality of sub-pixels. The display device 50 sets the cathode 15 to a predetermined potential, and drives each cathode on the substrate 60 by a TFT (not shown) formed on the substrate 60 for each sub-pixel, so that each light emitting element emits light. Thus, the display device 50 can perform full-color display.
[0129] The display device 50 includes a bank 61. The bank 61 is formed on the substrate 60, and is divided into sub-pixels from the anode of each light-emitting element to the electron transport layer of the display device 50. For example, in order to reduce the electric field concentration near the end of the anode of each light-emitting element, the bank 61 may be formed at a position overlapping with the end of each anode. The bank 61 may be made of a resin material such as polyimide, or may include a photosensitive resin.
[0130] The display device 50 of this embodiment can also be manufactured by preparing the substrate 60 and then forming each light-emitting element on the substrate 60 by the same method as the method of manufacturing the light-emitting element 1 of the first embodiment.
[0131] More specifically, for example, first, after forming a thin film of an anode on a substrate 60, each sub-pixel is patterned. Next, a dam 61 is formed on the substrate 60 and each anode by photolithography using a photosensitive resin or the like. Next, a hole injection layer, a hole transport layer, a light-emitting layer, and an electron transport layer of each light-emitting element are formed in each sub-pixel by coating by an inkjet method or the like, or patterning by photolithography using a photosensitive resist or the like. Next, a common cathode 15 is formed for a plurality of sub-pixels by a sputtering method or the like. As described above, a display device 50 can also be manufactured.
[0132] In addition, the luminescent color of each luminescent layer can also be changed by changing the particle size of the quantum dots contained in the film-forming layer in the formation process of each luminescent layer. In addition, in the formation process of each electron transport layer, the proportion of the second material portion 31 formed on the surface 30S of the nanoparticles 30 in each electron transport layer or the thickness of the second material portion 31 can be changed by changing the concentration of the second material added to the first solution.
[0133] Fig.10 yes Fig. 9 An energy band diagram in each layer of display device 50 is shown. Fig.10 In the figure, the Fermi levels of the anode 10 and the cathode 15 are represented. Fig.10, the band gaps of the hole injection layer 11R, the hole injection layer 11G, the hole injection layer 11B, the hole transport layer 12R, the hole transport layer 12G, the hole transport layer 12B, the red light-emitting layer 13R, the green light-emitting layer 13G, the blue light-emitting layer 13B, the electron transport layer 14R, the electron transport layer 14G and the electron transport layer 14B are represented respectively.
[0134] As mentioned above, Fig. 9 The red light emitting element 1R, the green light emitting element 1G, and the blue light emitting element 1B shown have the same configuration as each other except for the emission color of each light emitting layer and the configuration of each electron transport layer. Fig.10 In the embodiment, the hole injection layer 11R, the hole injection layer 11G and the hole injection layer 11B are made of the same material. Fig.10 In the embodiment, the hole transport layer 12R, the hole transport layer 12G and the hole transport layer 12B use the same material. Therefore, the band gap of the hole injection layer 11R, the band gap of the hole injection layer 11G and the band gap of the hole injection layer 11B are the same. Similarly, the band gap of the hole transport layer 12R, the band gap of the hole transport layer 12G and the band gap of the hole transport layer 12B are the same.
[0135] In addition, in this embodiment, as described above, the ratio of the cross-sectional area of the second material to the cross-sectional area of the first material in the electron transport layer of each light-emitting element is changed for each emission wavelength of each light-emitting element. Fig.10 , for convenience of explanation, the electron transport layer 14R, the electron transport layer 14G, and the electron transport layer 14B have the same configuration and show the band gap when the same materials are used.
[0136] In addition, Fig.10 In FIG. 1 , for the red light-emitting layer 13R, the band gap of the red quantum dot 40R is indicated, for the green light-emitting layer 13G, the band gap of the green quantum dot 40G is indicated, and for the blue light-emitting layer 13B, the band gap of the blue quantum dot 40B is indicated. Fig.10 In FIG. 1 , for the electron transport layer 14 , the band gaps of the nanoparticles 30 made of the first material and the second material portion 31 made of the second material are shown. Fig.10 The energy band diagram also shows the energy levels of each layer based on the vacuum energy level Evac.
[0137] As mentioned above, the emission color of each quantum dot can be changed by changing the particle size of the quantum dot. The particle size of the quantum dot becomes smaller as the emission wavelength becomes shorter. Fig. 9 As shown, the particle size of green quantum dots 40G is smaller than that of red quantum dots 40R, and the particle size of blue quantum dots 40B is smaller than that of green quantum dots 40G. Therefore, as the emission wavelength becomes shorter, it becomes more difficult for holes to be injected into the light-emitting layer, resulting in an excess of electrons.
[0138] In addition, the ionization potential of the hole transport layer 12 is set to IP1, the ionization potential of the red light-emitting layer 13R is set to IPR, the ionization potential of the green light-emitting layer 13G is set to IPG, and the ionization potential of the blue light-emitting layer 13B is set to IPB. Fig.10 As shown, in this embodiment, the ionization potential IP1 of the hole transport layer 12 is smaller than the ionization potential IPR of the red light emitting layer 13R, the ionization potential IPG of the green light emitting layer 13G, and the ionization potential IPB of the blue light emitting layer 13B.
[0139] In addition, the ionization potential IP1 of the hole transport layer 12 is represented by the absolute value of the energy difference between the vacuum level Evac and the upper end (VBM) of the valence band of the hole transport layer 12. In addition, the ionization potential IPR of the red light-emitting layer 13R is represented by the absolute value of the energy difference between the vacuum level Evac and the VBM of the red light-emitting layer 13R. The ionization potential IPG of the green light-emitting layer 13G is represented by the absolute value of the energy difference between the vacuum level Evac and the VBM of the green light-emitting layer 13G. The ionization potential IPB of the blue light-emitting layer 13B is represented by the absolute value of the energy difference between the vacuum level Evac and the VBM of the blue light-emitting layer 13B.
[0140] Generally, in a charge injection type light-emitting element, the height of the potential barrier when holes are injected from a first layer into a second layer adjacent to the first layer is equivalent to the energy difference between the VBM of the second layer and the VBM of the first layer, which is expressed as the energy obtained by subtracting the ionization potential of the first layer from the ionization potential of the second layer.
[0141] like Fig. 9 As shown, the ionization potential IPB of the blue light-emitting layer 13B is greater than the ionization potential IPR of the red light-emitting layer 13R and the ionization potential IPG of the green light-emitting layer 13G. Therefore, the potential barrier for injecting holes from the hole transport layer 12 into the blue light-emitting layer 13B is greater than the potential barrier for injecting holes from the hole transport layer 12 into the red light-emitting layer 13R and the potential barrier for injecting holes from the hole transport layer 12 into the green light-emitting layer 13G. In addition, the band gap increases as the particle size decreases. As shown in FIG. Fig.10 As shown, the band gap of the blue light emitting layer 13B is larger than that of the green light emitting layer 13G, and the band gap of the green light emitting layer 13G is larger than that of the red light emitting layer 13R. Therefore, as described above, the shorter the emission wavelength, the more difficult it is to inject holes into the light emitting layer, resulting in an excess of electrons.
[0142] Therefore, in this embodiment, as described above, the ratio of the cross-sectional area of the second material to the cross-sectional area of the first material in the electron transport layer 14B is made larger than the ratio of the cross-sectional area of the second material to the cross-sectional area of the first material in the electron transport layer 14G and the ratio of the cross-sectional area of the second material to the cross-sectional area of the first material in the electron transport layer 14R. As a result, in the blue light-emitting element 1B, the electron suppression effect can be enhanced compared with the green light-emitting element 1G and the red light-emitting element 1R.
[0143] In addition, by making the ratio of the cross-sectional area of the second material in the electron transport layer 14G to the cross-sectional area of the first material greater than the ratio of the cross-sectional area of the second material in the electron transport layer 14R to the cross-sectional area of the first material, the electron suppression effect can be enhanced in the green light-emitting element 1G compared to the red light-emitting element 1R.
[0144] In this way, by changing the ratio of the cross-sectional area of the second material to the cross-sectional area of the first material to enhance the electron suppression effect, the carrier balance can be adjusted and the driving voltage can be further reduced.
[0145] In addition, Fig.10 In FIG. 1 , the electron affinity of the red light emitting layer 13R is EAR, the electron affinity of the green light emitting layer 13G is EAG, and the electron affinity of the blue light emitting layer 13B is EAB. Fig.10 As shown, in this embodiment, the electron affinity EAB of the blue light-emitting layer 13B is smaller than the electron affinity EAG of the green light-emitting layer 13G, and the electron affinity EAG of the green light-emitting layer 13G is smaller than the electron affinity EAR of the red light-emitting layer 13R.
[0146] Therefore, the electron injection barrier of the electron transport layer 14B from the second material portion 31B to the blue light-emitting layer 13B is greater than the electron injection barrier of the electron transport layer 14G from the second material portion 31G to the green light-emitting layer 13G. In addition, the electron injection barrier of the electron transport layer 14G from the second material portion 31G to the green light-emitting layer 13G is greater than the electron injection barrier of the electron transport layer 14R from the second material portion 31R to the red light-emitting layer 13R. Fig.10 As shown, the electron transport layer 14R, the electron transport layer 14G, and the electron transport layer 14B have the same structure. When the same materials are used, the driving voltage of the green light-emitting element 1G is higher than the driving voltage of the red light-emitting element 1R, and the driving voltage of the blue light-emitting element 1B is higher than the driving voltage of the green light-emitting element 1G. Fig.10, the case where the electron affinity EAR of the red light emitting layer 13R, the electron affinity EAG of the green light emitting layer 13G, and the electron affinity EAB of the blue light emitting layer 13B are greater than the electron affinity EA3 of the second material portion 31 is shown. However, assuming that the electron affinity EA3 of the second material portion 31 is made of various materials, there is a case where the electron affinity EAR of the red light emitting layer 13R, the electron affinity EAG of the green light emitting layer 13G, and the electron affinity EAB of the blue light emitting layer 13B are smaller than the electron affinity EA3 of the second material portion 31. Here, the case where the electron affinity of the light emitting layer is smaller than the electron affinity EA3 of the second material portion 31 is described as an example.
[0147] In this case, in order to further reduce the applied voltage of the display device 50, it is desirable to further reduce the driving voltage of the blue light-emitting layer 13B. According to the present embodiment, by providing the second material portion 31B on the surface of the nanoparticle 30B as described above, it is possible to suppress electron injection as described above, and reduce the barrier of electron injection from the second material portion 31B of the electron transport layer 14B to the blue light-emitting layer 13B, thereby reducing the driving voltage of the blue light-emitting element 1B.
[0148] According to the research of the inventors of the present application, for example, even when a light-emitting material that does not use cadmium and emits blue light is used, the driving voltage of the blue light-emitting element 1B can be reduced by providing a second material portion 31B composed of an inorganic second material having an electron transport ability lower than that of the first material on the surface of a nanoparticle 30B composed of a first material.
[0149] Furthermore, it was confirmed that in step S7, by adding magnesium acetate tetrahydrate at 50 mol % relative to the solute of the first solution, the driving voltage could be further reduced compared to the case where magnesium acetate tetrahydrate was added at 30 mol % relative to the solute of the first solution.
[0150] The present disclosure is not limited to the above-mentioned embodiments, and various changes can be made within the scope of the claims. The embodiments obtained by appropriately combining the technical solutions disclosed in different embodiments are also included in the technical scope of the present disclosure. Moreover, by combining the technical means disclosed in each embodiment, new technical features can be formed. Description of Reference Numerals
[0151] 1, 2, 3: Light-emitting components 1B: Blue light emitting element 1G: Green light emitting element 1R: Red light emitting element 10, 10B, 10G, 10R: Anode 11, 11B, 11G, 11R: hole injection layer 12, 12B, 12G, 12R: hole transport layer 13: Luminous layer 13B: Blue light-emitting layer (light-emitting layer) 13G: Green light-emitting layer (light-emitting layer) 13R: Red light emitting layer (light emitting layer) 14, 14B, 14G, 14R, 16: Electron transport layer (intermediary layer) 15" cathode 20, 20B, 20G, 20R, 21: Nanoparticle structures 30, 30B: Nanoparticles 30S: Surface 31, 31B, 31G, 31R, 32: Second material department 50: Display device 60: Substrate
Claims
1. A light emitting element, characterized in that: It includes: anode; cathode; a light-emitting layer located between the anode and the cathode; as well as an intervening layer located between the light-emitting layer and the cathode, The intermediary layer has: at least one nanoparticle composed of a first material comprising a metal oxide; and The second material portion is formed on at least a portion of the surface of the nanoparticle and is composed of an inorganic second material, wherein the second material has lower electron transport capability than the first material.
2. A light emitting element, characterized in that: It includes: anode; cathode; a light-emitting layer located between the anode and the cathode; as well as an intervening layer located between the light-emitting layer and the cathode, The intermediary layer has: at least one nanoparticle composed of a first material, the first material comprising at least one of the group consisting of zinc oxide, magnesium zinc oxide, lithium zinc oxide, titanium oxide, and strontium titanium oxide; as well as The second material portion is formed on at least a portion of the surface of the nanoparticle and is composed of a second material, wherein the second material includes at least one of the group consisting of magnesium oxide, zirconium oxide, aluminum oxide, yttrium oxide, silicon oxide, zinc sulfide, magnesium zinc sulfide and strontium sulfide.
3. A light emitting element, characterized in that: It includes: anode; cathode; a light-emitting layer located between the anode and the cathode; as well as an intervening layer located between the light-emitting layer and the cathode, The interposer is formed by the following method, the method comprising: Synthesis of a first solution, the first solution containing at least one nanoparticle, the at least one nanoparticle being composed of a first material; synthesizing a second solution by adding a second material different from the first material to the first solution; forming a second material portion, by subjecting the second solution to ultrasonic treatment to form the second material portion on at least a portion of the surface of the nanoparticle, wherein the second material portion is composed of the second material; and The coating of the second solution has at least one of the nanoparticles having the second material portion formed thereon.
4. The light emitting element according to any one of claims 1 to 3, characterized in that The second material has lower electron mobility than the first material.
5. The light emitting element according to any one of claims 1 to 4, characterized in that: The second material has a lower electron affinity than the first material.
6. The light emitting element according to any one of claims 1 to 5, characterized in that: The first material contains magnesium zinc oxide, and the second material contains a metal oxide.
7. The light emitting element according to claim 6, characterized in that The second material includes magnesium oxide.
8. The light emitting element according to any one of claims 1 to 7, characterized in that: The light emitting layer has a light emitting material having a ratio of cadmium atoms of 0.01 wt % or less in total atoms.
9. The light emitting element according to any one of claims 1 to 8, characterized in that: The light-emitting element includes a hole transport layer, which is located between the anode and the light-emitting layer and includes an inorganic material.
10. The light emitting element according to any one of claims 1 to 8, characterized in that: The light emitting element comprises: a hole transport layer, located between the anode and the light-emitting layer and comprising an organic material; The hole injection layer is located between the anode and the hole transport layer and comprises an inorganic material.
11. The light emitting element according to any one of claims 1 to 10, characterized in that: In a cross section of the nanoparticle, the second material portion covers 10% or more of an outer circumference of the nanoparticle.
12. The light emitting element according to any one of claims 1 to 11, characterized in that: In a cross section of the nanoparticle, the second material portion is arranged in an island shape on the periphery of the nanoparticle.
13. The light emitting element according to claim 12, characterized in that: In a cross section of the nanoparticle, the second material portion covers 90% or less of an outer circumference of the nanoparticle.
14. A display device, characterized in that: It has: substrate; and The red light emitting element, the green light emitting element and the blue light emitting element on the substrate, At least one of the red light-emitting element, the green light-emitting element, and the blue light-emitting element is the light-emitting element according to any one of claims 1 to 13.
15. The display device according to claim 14, characterized in that At least two of the red light emitting element, the green light emitting element and the blue light emitting element are light emitting elements according to any one of claims 1 to 13, For any two of the at least two light-emitting elements, the light-emitting element with a shorter light-emitting wavelength is set as a short-wavelength element, and the light-emitting element with a longer light-emitting wavelength is set as a long-wavelength element, In the cross section of the interposer, a ratio of a cross-sectional area of the second material to a cross-sectional area of the first material is smaller in the long wavelength element than in the short wavelength element.
Citation Information
Patent Citations
Quantum dot-light-emitting devices comprising alloyed nanoparticle electron transport layer and method for fabricating the same
KR1020160033520A